Service innovation enabled by Internet of Things and cloud computing - a service-dominant logic perspective - Nittala, Sreenivasa S. Sharma; Bharadwaj, Sangeeta Shah; Tripathi, Shiv S.; Seif, Heiko (Technology analysis & strategic management, 2022)
Service innovation in the context of systems having layered-modular and service-oriented architecture is through innovation in the constituent components. Many of these components are platforms owned by different organisations. The combination of complementary paradigms of Internet of Things (IoT) and Cloud computing has a huge potential for creating innovative services. While technical aspects of this integration are addressed in extant research, the process of service innovation has not received much attention. This process brings multiple organisations into play and an IT solutions and services organisation (focal firm) designs a domain-specific platform leveraging the IoT and cloud platforms. This study explores this process in the aviation domain using Service-Dominant (S-D) logic with its three dimensions - Service Eco-system, Service Platform and Value Co-creation. S-D logic axioms are mapped to gain understanding of the micro-theoretical level elements and to develop operational principles for the orchestration of the service innovation process.